Influenza Vaccination and Treatment with Antiviral Agents Among Hospitalized Adults in the 2014–2015 and 2015–2016 Influenza Seasons. (4th October 2017) - E Segaloff, Hannah; Petrie, Joshua G; Malosh, Ryan E; Cheng, Caroline K; Ferdinands, Jill M; Lamerato, Lois; Lauring, Adam S; Monto, Arnold S; Martin, Emily T
Abstract: Background: Vaccination and treatment with neuraminidase inhibitors can reduce incidence and severity of influenza. Observational studies suggest antiviral treatment reduces influenza symptom duration and severe outcomes among hospitalized patients. The interaction of the effects of vaccination and antiviral treatment against severe influenza has not been established. Methods: We used data from a test-negative influenza vaccine effectiveness study. The parent study enrolled adults admitted to two hospitals in Michigan with an acute respiratory illness of ≤10 days duration during the 2014–2015 and 2015–2016 influenza seasons. Respiratory swabs from enrolled patients were tested for influenza by RT-PCR; influenza-positive individuals were included in this analysis. We evaluated predictors of vaccination and antiviral treatment using logistic regression. We also assessed the association between antiviral treatment and hospital length of stay (LOS) using linear regression models stratified by vaccination status. Results: We included 200 individuals in the analysis; 103 (51.5%) were vaccinated and 135 (67.5%) were treated with antivirals. Significant predictors of vaccination included age ≥65, white race, a Charlson comorbidity index (CCI) score ≥3, study site, and increased past-year health care visits. Antiviral treatment varied by study site and was more common in the 2015–2016 season and among those aged 18–49. Vaccination was not associated with antiviral treatment or with time from illness onset to treatment. Antiviral treatment was associated with reduced LOS (percent change in LOS: −23.6% (−39.2%, −4.1%), P = 0.02) among vaccinated participants but not among unvaccinated participants (21.1% (−10.9%, 64.8%), P = 0.22) after adjustment for sex, age, influenza subtype, site, CCI, frailty, and past-year health care contacts. When an interaction term was used in lieu of stratification the interaction was significant ( P = 0.01). This difference in antiviral effectiveness by vaccination status held across age groups, but was most dramatic for those aged 18–49. Conclusion: Vaccinated individuals were more likely than unvaccinated individuals to benefit from antiviral treatment. This finding warrants confirmation in other populations. Disclosures: A. S. Monto, sanofi pasteur: Grant Investigator, Research grant. Novartis: Consultant, Consulting fee. Protein Sciences: Consultant, Consulting fee. E. T. Martin, Pfizer: Scientific Advisor, Research grant. Merck: Scientific Advisor, Research grant. Multiparty Group For Advice on Science: Scientific Advisor, Research grant.